Programming for TV, radio, and the Internet : - Perebinossoff, Philippe. (Focal Press, 2005)
Where do program ideas come from? How are concepts developed into saleable productions? Who do you talk to about getting a show produced? How do you schedule shows on the lineup? What do you do if a series is in trouble? The answers to these questions, and many more, can be found in this comprehensive, in-depth look at the roles and responsibilities of the electronic media programmer. Topics include: Network relationships with affiliates, the expanded market of syndication, sources of programming for stations and networks, research and its role in programming decisions, fundamental appeals to an audience and what qualities are tied to success, outside forces that influence programming, strategies for launching new programs or saving old ones. Includes real-life examples taken from the authors' experiences, and 250+ illustrations!